Nepal’s National Education Policy: Challenges, Progress and Future Directions - Lal, Suruchi (Political Science Journal, 2025)
Nepal's National Education Policy (NEP) serves as a transformative framework for achieving inclusive, equitable, and quality education while aligning with global standards such as Sustainable Development Goal 4 (SDG4). Recognizing education as a catalyst for socio-economic progress, the NEP emphasizes universal access, lifelong learning, and the integration of vocational and technical education. This study aims to critically examine the NEP’s historical evolution, its alignment with global goals, implementation challenges, and its contributions to addressing educational disparities and enhancing quality. The study adopts a qualitative methodology, relying on an extensive review of government documents, academic literature, and international reports. Thematic analysis was employed to evaluate the NEP's effectiveness in improving access, equity, and quality, alongside its potential to address youth unemployment through vocational education. The study shows notable progress in increasing literacy rates, school enrolment, and vocational training opportunities. However, challenges persist, including regional disparities, gender inequalities, inadequate teacher training, and insufficient coordination in decentralized governance. The results highlight the need for targeted interventions to bridge gaps in educational quality and equity. Achieving the NEP's objectives requires sustained investments, improved teacher training, strengthened public-private partnerships, and expanded digital infrastructure. Addressing these challenges will enable the NEP to foster a resilient, equitable, and inclusive education system that supports Nepal’s sustainable development goals.